Teach a fisherman to market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
seminar co-organised by the Spanish Ministry of Agriculture, Fisheries and Food and CTA, in Spain in June 2000